Pengaruh Kepemilikan Institusional, Likuiditas, Pertumbuhan Penjualan, dan Ukuran Perusahaan terhadap Kinerja Keuangan: (Studi Empiris pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2020 – 2024) - Nicholaus Bayu Eka Pratama; Prita Andini (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze in more depth the influence of institutional ownership, liquidity, sales growth, and company size on the financial performance of property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period, with a population of 94 companies. The research data are sourced from officially published annual financial reports. The sampling technique used a purposive sampling method based on certain criteria, resulting in 215 observational data from 43 companies that met the research requirements. Data analysis was conducted using a quantitative approach using multiple linear regression tests with the assistance of Statistical Package for the Social Sciences (SPSS) version 22 software. The results show that institutional ownership and company size have a positive and significant influence on financial performance, meaning that the greater the institutional ownership and company size, the higher the resulting financial performance. However, liquidity and sales growth were shown to have no effect on financial performance, indicating that a company's ability to meet short-term obligations or an increase in sales volume does not always reflect better financial condition. Thus, it can be concluded that internal factors in the form of institutional ownership and company size are more dominant determinants in determining the financial performance of companies in the property and real estate sector in Indonesia compared to liquidity factors and sales growth.